Business Dynamism and Economic Growth: US Regional Evidence - Casares, Miguel; Khan, Hashmat (Senate Hall, 2016)
We document empirical evidence linking regional growth in the United States over the last 25 years with entrepreneurial activity, or 'business dynamism'. The main data source is the Business Dynamics Statistics (BDS) released by the US Census Bureau. We uncover a new stylised fact: across US states, it is not the level but rather the change in business entry rate that has a significant positive relationship with regional growth. Specifically, those states that have experienced a relatively large decline in the entry rate also have had weaker economic growth. Besides, our research confirms earlier found stylised facts such as the high correlation between entry and exit rates, and the convergence hypothesis which holds across the states. We conduct a number of robustness checks to establish these new and old stylised facts and conditional correlations in the BDS data. Keywords: business dynamism, entry-exit rates, economic growth
Keywords: Business Dynamism|Entry-Exit Rates|Economic Growth